A CRITICAL ANALYSIS OF BAL CHATURBHADRA CHURNA IN MANAGEMENT OF CHILDHOOD DISORDERS- EVIDENCES FROM AYURVEDA (International Journal of Ayurveda and Pharma Research, 2020)
Bal chaturbhadra churna is a poly-herbal formulation used in pediatric practice in Ayurveda especially in the treatment of vomiting, diarrhea, fever and respiratory disorders. The human clinical dose of Bal chaturbhadra churna is 1000 mg per day. It is prepared by mixing equal proportions of rhizome of Cyperus rotundus Linn. (Cyperaceae), fruit of Piper longum Linn. (Piperaceae), root of Aconitum heterophyllum Wall. ex. Royale. (Ranunculaceae) and gall of Pistacia integerrima Stew. Ex. Brandis. (Anacardiaceae). Aims and objectives: Critical analysis of Bal chaturbhadra churna in management of childhood disorder. Material and Methods: Various Ayurveda classics and studies published in journals related to use of Bal chaturbhadra churna in management of childhood disorder are reviewed and analyzed. Discussion: Contents of Bal chaturbhdra churna are mostly katu rasa, laghu guna, usna veerya and also deepana, pachana, krimighna, visaghna, hridya, ruchya, vrisya, rasayana, rochana, sthoulyahara, trisnanigrahana, tvakadosahara, jwaraghna etc. properties. Therefore due to presence of these qualities, it is used in vomiting, diarrhea, fever and respiratory disorders. According to studies published in journals, it is beneficial as immuno-modulator, anti inflammatory, anti spasmodic, anti asthmatic activity, anti bacterial activity, antidiabetic activity, antioxidant activity, anti-fungal activity, hepatoprotective action, analgesic activity.  Conclusion: Present review reveals Bal chaturbhadra churna is quite safe for administration among Children and therefore can be used in various ailments in children which can limit the irrational use of antibiotics in them.